Development of an Entrepreneurship E-Book with a Realistic Approach to Improve Student Fashionpreneurship Competence - Retnasari, Dian; Nurlita, Asri Andarini (Journal of Research and Educational Research Evaluation, 2024)
Fashionpreneurship is one of the competencies that fashion education study program students must possess. Therefore, it is essential to have an e-book with a realistic approach as a companion media that can help improve student competence. The study aimed to produce an e-book and determine the feasibility of e-books with a realistic approach. This type of research is development research (Research & Development). This research uses the 4D development model: define, design, develop, and disseminate. The data collection method used observation, document study, interview, and questionnaire. Data about the feasibility of e-books were analyzed using quantitative descriptive statistics. The results of this study indicate the feasibility of teaching materials based on the assessment of material experts, media experts, small-scale trials, and large-scale trials, which obtained very feasible category results. Thus, the developed entrepreneurship e-book can be used by students to improve their fashionpreneurship competencies.